Loss Of Correction By Segmental Pedicle Screws Compared To Hybrid Fixation In Adolescent Idiopathic Scoliosis - Mustufa Pervez; Imtiaz A. Hashmi; Sohail Rafi; Idrees Shah; Aqeel A. Memon (ziauddin University, 2024)
Objective: This study was conducted to collate and compare a 1 year post-surgical radiographic outcome of posterior spinalinstrumentation and correction in the coronal plane with the use of pedicle screws against hybrid fixation in patients with adolescent idiopathic scoliosis. Methods: Cross-sectional study involving 34 patients who underwent scoliosis correction. The variables were measured pre-operatively, immediately post surgery and in two 6 monthly OPD follow-ups. Data analysis of data was conducted in SPSS version 20. Results: Average major curve was corrected from 58.0 ± 13.0° pre-op to 16.0 ± 9.0° using pedicle screws fixation and increased to 18.4 ± 8.6° at first year follow-up and using hybrid construct, thenormal major curve was corrected from 62.0 ± 13.0° pre-op to 18.0 ± 8.0° and increased to 22 ± 9°. By 1 year of follow-up, differences were apparent between the two groups considering the curvature in the coronal plane. Conclusion: Cobbs angles between pre-operative and post operative correction and 1-year radiographic follow-up evaluation was better in the instrumentation fixation using pedicle screws compared to hybrid instrumentation. Using pedicle screws there was a correction loss of 12.5% as compared to the 16.6% using hybrid fixation Pedicle screw instrumentation. Pedicle screw fixation also has the advantage of allowing three dimensional correction of deformity. Key Words: Adolescent, Scoliosis, Pedicle Screws